Photodynamic Therapy in Otorhinolaryngology: Current Evidence, Clinical Applications and Future Perspectives - Mierzejewska, Zofia Aneta; Zawadzka, Magdalena; Marszałek, Dominika; Czudowska, Michalina; Kurzątkowska, Klaudia; Bystros, Aleksandra Natalia; Drozdowska, Marta; Borychowska, Emilia; Ocimek, Aleksandra; Gwóźdź, Karolina (Quality in Sport, 2026)
Photodynamic therapy (PDT) is an interesting approach for the treatment of various otorhinolaryngological diseases, primarily when conventional therapeutic options are restricted by antibiotic resistance, biofilms, or high relapse rates. This systematic review critically analyzes 20 open-access clinical, microbiological, and experimental studies with PDT reported between 1992 and 2025. Initial clinical pilot data suggested a well-tolerated agent that improved symptoms and disrupted biofilm. In chronic and recurrent tonsillitis, existing evidence also indicates a decrease in microbial load, clinical improvement, and (in some cases) reduced infection over time. Case-based studies provide additional evidence for PDT as a non-invasive therapeutic option in pharyngotonsillitis. PDT decreases lesion size and delays recurrence in recurrent respiratory papillomatosis when applied adjunctively to surgery. These indicate potential utility for persistent viral conditions, including HPV-related diseases. Further studies on PDT indicate the reduction of SARS-CoV-2 colonization during the COVID-19 pandemic. PDT nasal application decreases viral shedding. New technologies, such as better photosensitizers, nanoparticle carrier delivery systems and improved light-delivery devices, have broadened the application of PDT in anatomically complex areas relating to ears, nose and throat (ENT). The above have improved treatment selectivity, reduced photo toxicity and increased the antimicrobial effect. Despite these promising results, the available evidence is restricted by small sample size, heterogeneity of the protocols and inconsistency of outcome measures. Larger, uniform clinical trials are required to define the optimal treatment features and their therapeutic value. Due to its antiviral, antimicrobial, and antibiofilm potential in otorhinolaryngology, there may well be opportunities to further develop PDT field as a beneficial adjunctive treatment.